Implication of Digital Economy and Financial Technology Towards Performance of Financial Services Sector in Indonesia - Kusuma Ratnawati; Christin Susilowati (MIX: JURNAL ILMIAH MANAJEMEN, 2022)
Objectives: This study aims to understand the relationship between financial technology, digital economy, and performance of the financial services sector; as well as to find out the role of digital economy as a mediator in the relationship between financial technology and performance of the financial services sector.Methodology: This study uses a quantitative explanatory approach. The population of this study is financial services sector companies in Indonesia, which is determined using purposive sampling as a method of sampling design. The data used in this study is a secondary data with the research period from 2015-2019 and a total number of 50 data. The data analysis used in this study is path analysis.Finding: The mediating role of the digital economy that influences the relationship between financial technology and the performance of the financial services sector. The influence of financial technology in driving the growth of the digital economy creates a momentum for economic growth and development.Conclusion: The results explained that financial technology and the digital economy has a significant influence on performance of the financial services sector.